Must know high school trigonometry - McCune, Sandra Luna; Clark, William D. (New York: McGraw-Hill, 2020)
Every school subject has must know ideas, or essential concepts, that lie behind it. This book will use that fact to help you learn in a unique way. Most study guides start a chapter with a set of goals, often leaving the starting point unclear. In Must Know High School Trigonometry, however, each chapter will immediately introduce you to the must know idea, or ideas, that lie behind the new trigonometry topic. As you learn these must know ideas, the book will show you how to apply that knowledge to solving trigonometry problems. Focused on the essential concepts of trigonometry, this accessible guide will help you develop a solid understanding of the subject quickly and painlessly. Clear explanations are accompanied by numerous examples and followed with more challenging aspects of trigonometry. Practical exercises close each chapter and will instill you with confidence in your growing trigonometry skills
Keywords: Trigonometry -- Problems, exercises, etc